Effect of Size of Stem Cuttings on Juvenile Growth of Populus ciliata Wall. ex Royle - Deol, G. S.; Khosla, P. K. (Indian Forester, 1983)
Effect of size of stem cuttings on first season's growth of Populus ciliata was observed in a nursery trial. Increase in the diameter as well as length of the cuttings significantly increased number of roots, average root length, number of leaves and average leaf area resulting in dilfferntial shoot growth. The increased plant growth with larger sized cuttings (mid dia = 18 mm, length = 30 cm, D2L3) suggests direct field planting ot these cuttings at moisture rich sites. However, for clonal propagation at nursery stage, stem cuttings with 22.5 cm length and 14 mm mid dia are recommended.